Efektivitas Pemanfaatan Teknologi Augmented Reality (AR) Dalam Pendidikan Kesiapsiagaan Bencana Banjir Di Kelurahan Lepo-Lepo Kota Kendari - Agil Lestari; Kasim, Safril; Sudia, La Baco (Universitas Budi Luhur, 2024)
Floods are one of the most common disasters in Indonesia, causing significant damage and loss of life in recent years. It is essential to improve community preparedness for such events. Augmented Reality (AR) technology, which integrates 2D and 3D elements, offers an interactive learning experience through smartphones, effectively presenting visual, audio, and video information. This study aims to evaluate the effectiveness of AR technology in enhancing flood preparedness in the Lepo-Lepo Subdistrict, Baruga District. The methods employed include observation, interviews, questionnaires, and literature reviews. The results indicate that the AR-based BeWary application effectively increased community knowledge and preparedness for flood risks, with statistically significant results. However, there are suggestions for further development, such as enhancing application features and more targeted strategies. Factors influencing the effectiveness of AR include limited technology access, challenges in adapting to new technologies, and perceptions that affect interest in using additional technologies. Additionally, time constraints, digital literacy, and technical skills are key factors to consider in implementing AR for flood preparedness education.